Intravitreal bevacizumab injections can release vitreomacular adhesions in eyes with persistent diabetic macular edema and vitreomacular adhesions - Al Judaibi, Ramzi M. (2012)
Purpose: to report cases of persistent diabetic macular edema (DME) with vitreomacular adhesions (VMA) that responded to intravitreal bevacizumab (IVB) injection with separation of the VMA and complete or significant resolution of DME Methods: Three eyes of three patients were diagnosed with persistent DME and VMA following focal laser therapy based on typical clinical, angiographic, and spectral-domain optical coherence tomography (SD-OCT, Spectralis, Heidelberg, Germany) findings. A trial of IVB was attempted prior to proceeding with pars plana vitrectomy (PPV) to address the VMA. Results: All eyes disclosed cystoid macular edema with perifoveal vitreous separation and focal adhesion of the posterior hyaloid at the fovea on SD-OCT. Following one to three injections of IVB, SD-OCT showed complete separation of the VMA in all eyes with complete or significant resolution of the intraretinal fluid. Conclusions: Our findings suggest that a trial of intravitreal therapy, such as IVB, should be attempted in eyes with persistent DME and focal VMA before proceeding to PPV. The mechanical effect of the intravitreal injections may lead to separation of the VMA. This, together with the pharmacological effect of the injected agent, may lead to resolution of the DME as seen in the cases reported herein.